Germination dynamics of sesame seeds under salt stress - Batista Silva Rodrigues, Marilia; Rocha Limão, Rocha Limão; da Silva Santos, Adriana; da Silva Barbosa, Luana; Pinheiro Lopes, Kilson; Souto Ribeiro, Wellington (Comunicata Scientiae, 2022)
Sesame crops have large economic potential; however, the scarcity of good quality water in the Semiarid region of the Northeast of Brazil can affect production systems, which requires the search for cultivars that can better be adapted to the local conditions. In this context, the objective of this work was to evaluate the germination dynamics of sesame seed lots subjected to different electrical conductivities of the imbibition solution. The experiment was conducted at the Laboratory of Seeds and Seedling Analysis of the Federal University of Campina Grande, Pombal campus, Paraíba, Brazil. A completely randomized design was used, in an 8×6 factorial arrangement, corresponding to eight seed lots (BRS Seda; BRS Seda (S2); BRS G2 (S1); BRS G2 (S2); BRS G3 (S1); BRS G3 (S2); BRS G4 (S1) and BRS G4 (S2), where S1 and S2 represent the grown environments, saline (2.4 dS m-1) and non-saline, respectively; and six electrical conductivities of the imbibition solution (0.3; 1.2; 2.1; 3.0; 3.9; and 4.8 dS m-¹), with four replications. The variables seed germination, vigor, germination speed index, mean time for germination, mean germination speed, and radicle length were evaluated. The sesame seeds are sensitive to salinity, regardless of the lot analyzed and their germination power decreases when they are subjected to high salt concentrations.